A Genetically Modified, Enterovirus-Based Expression System in Human Induced Pluripotent Stem Cells for the Safe Study of Viral Pathomechanisms - Seebohm, Guiscard; Seebohm, Nathalie Strutz-; Hescheler, Jürgen; Peischard, Stefan (Archives of Clinical and Biomedical Research, 2025)
Coxsackievirus B3 (CVB3) is a major causative agent of viral myocarditis, a condition that can result in severe cardiac dysfunction and heart failure. Current research on CVB3 pathogenesis relies heavily on animal models or infectious virus systems, which are limited by biosafety requirements and translational challenges. To address these limitations, a novel human cell culture model based on induced pluripotent stem cells (hiPSCs) was developed, enabling controlled expression of viral genes without producing infectious particles. This system utilises a doxycycline-inducible Tet- On mechanism to regulate the expression of a modified CVB3 genome (CVB3ΔVP0-UTR), which lacks capsid protein functionality as well as 3´UTR and the 5´UTR, ensuring biosafety level 1 compliance. The results demonstrate that CVB3ΔVP0-UTR expression induces significant structural and functional changes in hiPSC-derived cardiomyocytes, including sarcomere disorganisation, reduced cell growth, impaired contractility, and extended contraction intervals. Furthermore, mitochondrial dysfunction was observed, characterised by fragmented mitochondrial networks, ROS accumulation, and decreased ATP production. These findings align with clinical features of CVB3-induced myocarditis and underscore mitochondrial dysregulation as a central pathological mechanism. This model provides a versatile platform for studying RNA virus pathogenesis and testing antiviral therapies. It offers significant advantages in terms of safety, controllability, and reproducibility while being adaptable to other RNA viruses. The present study underscores the potential of this model to further our understanding of viral myocarditis and to develop targeted therapeutic strategies.